The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1651-2227.2010.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the 1‐min Apgar score for survival at 23–26 weeks gestational age

Abstract: Despite successful resuscitation, infants between 23 and 26 weeks have a very poor prognosis for survival when presenting with bradycardia, cyanosis and no respiratory efforts (1-min Apgar = 1) at birth. According to our data, initiating active treatment for an infant at 23 weeks with bradycardia and apnoea is almost always unsuccessful, whereas by 26 weeks gestation, the chance of survival is higher than the probability of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
15
0
5
Order By: Relevance
“…The 1 minute Apgar score has been studied in various settings for predicting mortality in extremely preterm infants. For example, Genzel-Boroviczény et al 12 found in a study of inborn infants with gestational ages between 23 and 26 weeks that a 1 minute Apgar score of 1 or less was associated with a greater rate of mortality. Evans et al 13 found in a cohort of inborn infants with birth weight <1500 g or <32 weeks gestational age surviving to admission to the NICU in Australia and New Zealand that a 1 minute Apgar score of <4 predicted risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 minute Apgar score has been studied in various settings for predicting mortality in extremely preterm infants. For example, Genzel-Boroviczény et al 12 found in a study of inborn infants with gestational ages between 23 and 26 weeks that a 1 minute Apgar score of 1 or less was associated with a greater rate of mortality. Evans et al 13 found in a cohort of inborn infants with birth weight <1500 g or <32 weeks gestational age surviving to admission to the NICU in Australia and New Zealand that a 1 minute Apgar score of <4 predicted risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies have shown a correlation between Apgar score and outcome. Genzel-Boroviczény et al (10) reported in a single-center study of 234 infants born between 23 and 26 weeks that 1-min Apgar scores of 0 or 1 were associated with increased mortality, but that no clear association was seen between any 1-min Apgar score >1 and mortality risk in this gestational age group. Similarly, Singh et al (5) in a study of 102 infants 400-750 g admitted to a single center found that 1- or 5-min Apgar scores ≤3 were not significantly associated with increased risk of mortality or Bayley MDI or PDI < 70 at 2 years of age before or after adjustment for birth weight, gestational age, gender and race.…”
Section: Introductionmentioning
confidence: 99%
“…Unterschiede zeichnen sich hingegen in der Überlebensrate von Frühgeborenen mit einem Gestationsalter von 24 vollendeten Wochen ab, die in der amerikanischen NICHD-Kohorte im Gesamtzeitraum 1993-2009 bei 58 % (2 198/3 790) lag, [30] im deutschen Frühgeborenennetzwerk GNN 2010 bei 71,3 % (122/171), [31] und bundesweit 2012 entsprechend den vom AQUA-Institut veröffentlichten Zahlen bei 75,2 % (1 027/1 537) [29]. Bei Extremfrühgeborenen lassen der Nabelarterien-pH, [32] die Vitalität des Kindes unmittelbar nach der Geburt (mit Ausnahme extrem deprimierter Frühgeborener) [33] und das Ansprechen auf Erstversorgungsmaßnahmen keine brauchbaren prognostischen Aussagen zu [34,35]. Bei den Überlebenszahlen von Extremfrühgeborenen bestehen ebenso wie bei der neonatalen Mortalität deutliche Unterschiede zwischen verschiedenen Krankenhäusern, verschiedenen Regionen und verschiedenen Ländern [36,37].…”
Section: Rechtlicher Rahmen ▼unclassified